2017
DOI: 10.4038/cmj.v62i4.8568
|View full text |Cite
|
Sign up to set email alerts
|

Novel urinary biomarkers and their association with urinary heavy metals in chronic kidney disease of unknown aetiology in Sri Lanka: a pilot study

Abstract: Introduction Chronic kidney disease of unknown etiology (CKDu) has emerged as a significant public health problem in Sri Lanka. The role of environmental exposure to cadmium and arsenic in the aetiology of CKDu is still unclear. Identification of a panel of novel urinary biomarkers would be invaluable in the study of toxin mediated damage postulated to be the aetiology of CKDu.Objectives The aims of this study were to evaluate the profile of novel urinary biomarkers in CKDu patients and identify any associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
1
20
1
Order By: Relevance
“…Nanayakkara et al (2012) indicated a tubular marker, Alpha 1 microglobulin was elevated in more than 55% of CKDu cases and sensitive marker for early diagnosis and screening [30] and some studies have been described other interstitial nephropathies [31,32]. There were several studies investigating the effectiveness of tubular markers, including KIM1 and NGAL for screening and diagnosis of CKDu [30,[33][34][35]. Even though tubular manifestations like hypokalaemia, hyperuricaemia, renal tubular acidosis, have been described in CKDu [36].…”
Section: Plos Onementioning
confidence: 99%
“…Nanayakkara et al (2012) indicated a tubular marker, Alpha 1 microglobulin was elevated in more than 55% of CKDu cases and sensitive marker for early diagnosis and screening [30] and some studies have been described other interstitial nephropathies [31,32]. There were several studies investigating the effectiveness of tubular markers, including KIM1 and NGAL for screening and diagnosis of CKDu [30,[33][34][35]. Even though tubular manifestations like hypokalaemia, hyperuricaemia, renal tubular acidosis, have been described in CKDu [36].…”
Section: Plos Onementioning
confidence: 99%
“…The other main limitation is the lack of reference urinary biomarker levels that reflect subclinical damage in Sri Lankan nephropathy which prevents comparison among herbicide exposed and non-exposed farming communities. Despite recent studies [54,82], validation of normal levels of NGAL and KIM-1 in larger populations has not been carried out. Previously, Jayasumana et al (year) reported glyphosate and heavy metals (Cd, & As) as the main etiological factor in CKDu among farmers [27] and were shown to affect KIM-1 expression in an animal model [26].…”
Section: Discussionmentioning
confidence: 99%
“…Urine samples were analyzed for heavy metals and five biomarkers at the Harvard School of Public Health Trace Metals Analysis Laboratory (Boston, USA). 11 Urinary cadmium level in CKDu patients was lower than the farmer control and non farmer control groups [Mean (SD) 0.68 (0.39), 1.32 (1.27), 0.54 (0.31), respectively]. However, the farmer control group had a significantly higher urinary cadmium level (p<0.001) than the other two groups.…”
Section: Studymentioning
confidence: 82%
“…Only 32.4% had albumin-creatinine ratio (ACR) above 300 mg/g creatinine, the level which can be detected by the albustix method. 11 . CKDu patients had significantly elevated urinary levels of fibrinogen (p<0.001), clusterin (p<0.001), cystatin C (p<0.001) and beta-2 microglobulin (nine p<0.001) compared to the control groups.…”
Section: Early Diagnosis Of Ckdumentioning
confidence: 99%
See 1 more Smart Citation